Factors Influencing the Effectiveness of the System-Functional Approach in the Management of Innovative Development of Construction Companies - Sviatoslav KNIAZ; Nellі HEORHIADI; Marcel Kurt MAINKA; Svitlana MOROZ; Olena KALASHNYK; Anhelina SPITSYNA; Zoya RACHYNSKA; Ruslan SKRYNKOVSKYY; Yuriy SEMCHUK; Olha KOZAKEVYCH (Communications of International Proceedings, 2021)
The article identifies and classifies the factors that affect the effectiveness of the system-functional approach in the management of innovative development of construction companies. After conducting a survey of experts among construction companies, as well as applying methods of statistical processing of expert information, the gradation of factors according to the level of their significance was carried out and the correctness of the given expert assessments was substantiated.
Keywords: System-Functional Approach; Factors; Management; Innovative Development.